Determination of phenolic profile by HPLC-ESI-MS/MS and antibacterial activity of Eugenia platysema against mollicutes strains - Adrielli Tenfen, Diogo Alexandre Siebert, Daniel Spudeit, Caio Maurício Mendes de Cordova, Gustavo Amadeu Micke, Michele Debiasi Alberton (Journal of Applied Pharmaceutical Science, 2017)
This study evaluated the phenolic composition of the extract and fractions from E. platysema leaves, in addition to antibacterial activity against different types of bacteria, like mollicutes and cel wall bacteria. The crude extract (CHE) was partitioned with solvents to yield fractions of different polarities (dichloromethane, ethyl acetate, butanol and water). The chemical composition of CHE and its fractions were evaluated by HPLC-LC-ESI-MS/MS together with 76 standard phenolic compounds. Nine known compounds were identified for the first time from this species: hydroxybenzoic-O-hexoside acid [1], gallocatechin [2], syringic acid [3], 4-hydroxycinammic acid [4], salycilic acid [5], isoquercetin [6], isorhamnetin [7], luteolin-3’-O-glucuronide [8] and luteolin [9]. The evaluation of antibacterial activity was performed using the broth dilution method. The CHE and fractions of E. platysema were active against mollicutes strains, being the best result presented by the dichloromethane fraction against U. urealyticum, M. mycoides subsp. Capri and M. hominis (125 µg mL-1).
Keywords: Eugenia platysema, phenolic compounds, antibacterial activity, mollicutes.